Communication and cooperation in repeated games - Yu Awaya; Vijay Krishna (Theoretical Economics, 2019)
We study the role of communication in repeated games with private monitoring. We first show that without communication, the set of Nash equilibrium payoffs in such games is a subset of the set of ε-coarse correlated equilibrium payoffs (ε-CCE) of the underlying one-shot game. The value of ε depends on the discount factor and the quality of monitoring. We then identify conditions under which there are equilibria with "cheap talk" that result in nearly efficient payoffs outside the set ε-CCE. Thus, in our model, communication is necessary for cooperation.
Keywords: C73; 330; Repeated games; private monitoring; communication